Reconocimiento y medición de los elementos de los estados financieros según marco conceptual de las NIIF. - Armijos Pogo, Ana Gabriela (My University, 2022)
The present work presents how important the application of the concepts of measurement and recognition of the elements of the financial statements are in accordance with what is established in the Conceptual Framework of the IFRS, so that the financial information is reliable and therefore the decision. of decisions is correct. The proposed objective was to analyze the recognition and measurement of the elements of the financial statements through the resolution of a practical case, in order to demonstrate what is established in the Conceptual Framework of IFRS in the presentation of financial information. The methodology applied was with a qualitative approach, descriptive, hermeneutic method and using techniques such as review of bibliographic texts. Finally, with the resolution of the practical case raised, it follows that knowing how to correctly recognize and measure the elements of the financial statements makes the information reliable for users who wish to obtain information through them about the financial situation of a company.
El presente trabajo presenta lo importante que son la aplicación de los conceptos de medición y reconocimiento de los elementos de los estados financieros de acuerdo a lo establecido en el Marco Conceptual de las NIIF, para que la información financiera sea confiable y por lo tanto la toma de decisiones sea acertada. El objetivo planteado fue analizar el reconocimiento y medición de los elementos de los estados financieros a través de la resolución de un caso práctico, con el fin de demostrar lo establecido en el Marco Conceptual de las NIIF en la presentación de la información financiera. La metodología aplicada fue con enfoque cualitativo, de tipo descriptivo, método hermenéutico y utilizando técnicas como revisión de textos bibliográficos. Finalmente, con la resolución de caso práctico planteado, se deduce que el saber reconocer y medir correctamente los elementos de los estados financieros, hace que la información sea fiable para los usuarios que deseen informarse por medio de éstos sobre la situación financiera de una empresa.
Keywords: RECONOCIMIENTO; MEDICIÓN; MARCO CONCEPTUAL; ELEMENTOS